Shear strength analysis of slabs without transverse reinforcement under concentrated loads according to ABNT NBR 6118:2014 - A. M. D. SOUSA; M. K. EL DEBS (Revista IBRACON de Estruturas e Materiais, 2019)
Abstract Concentrated loads in slabs without transverse reinforcement, usual in highway bridges, result in the horizontal spreading of the shear force towards the supports, situation in which not all the slab width contributes in the shear strength. Based on this, the analytical models of shear strength and punching capacity in slabs may not be suitable to deal with this loading. Since this topic is not widely discussed in the national technical literature, the paper aims to present contributions to these analyses with a focus on the accuracy level of the shear strength analytical models recommended by ABNT NBR 6118:2014. Therefore, the models available in the Brazilian code were applied to an experimental database with 118 test results and the results obtained by the Brazilian and European codes were compared. The results demonstrated that, as presented in the Brazilian code, shear strength model in one-way slabs can lead to unsafe resistance predictions while the punching capacity model can lead to very conservative predictions. From the analysis, it is concluded that considering the reduction of the shear force, in the case of loads distributed in small areas close to the support in slabs, and the use of more suitable procedures to define the effective width, it is possible to improve the level of accuracy of relations between experimental and theoretical values, but this still leads to high percentages of unsafe predictions of resistance (> 40%).